Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The reality of applying total quality management at the University of Idlib  from the point of view of faculty and administrative academicsMr. Ahmad Mohamad Staif, Co-Prof. Siham Mustafa Abdulaziz, Dr. Hisham Farag Abd Alsid2. The Commitment of Secondary School Principals in Hodeidah City to Professional Ethics  from the Viewpoint of TeachersMr. Sadiq Abbas Saeed Ahmed, Prof. Abdul-Jabbar Al-Tayeb Ameen3. Digital transformation and its role in the quality of the educational process for primary school teachers in the city of RiyadhMs. Rahaf Ali Hamdi, Dr. Saud Ghassan Al-Bishr4. Ways and Obstacles to Professional Development of English Language Teachers in International Schools in Jeddah: Perspectives of Teachers and AdministratorsMs. Maysoon Mohmmed Eid , Dr. Rabab Saleh Alharbi5. The Degree of Arabic Language Teachers' Performance in Reinforcing Cooperative and Community Involvement Skills among Secondary Stage Students in MadinahCo-Prof. Mashael Saleh Al-Dosari, Ms. Reem Mahal Al-Ruwaythi6. The impact of the Item Response Theory (IRT) model on the accuracy of test score equatingDr. Easa Salamah Alhajory, Dr. Mohammed Mahmoud Abdel-Wahab7. The Situational Leadership Styles of Primary Grades Teachers in Early Childhood Schools  according to Hersey and Blanchard's Theory during the Changes in the Educational SystemsCo-Prof. Sama Fouad Khomais, Ms. Rana Hezam Al Sultan
Keywords: Journal of Educational and Psychological Sciences